2022
DOI: 10.1155/2022/5427837
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Carcinoma of Breast: Clinicopathological Characteristics, Management, and Survival

Abstract: Objective. To study clinicopathological features, treatment strategies, and prognosis of papillary carcinoma of breast. Material and Methods. Data from 58 patients were retrospectively reviewed from January 2010 to December 2016. Four types of papillary carcinoma (on final resected specimen) were included, i.e., invasive papillary carcinoma (IPC), intracystic (encapsulated) papillary carcinoma (EPC), solid papillary carcinoma (SPC), and papillary DCIS (ductal carcinoma in situ). Various features of the four ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…19 . Owing to the rarity of the disease and the complexity of its histological classi cation, there is no universally accepted consensus on the management of patients with invasive papillary carcinoma 20 . Interestingly, invasive papillary carcinoma is relatively more prevalent among males 21 which is consistent with our observation of invasive papillary carcinoma breast cancer subtypes in male patients.…”
Section: Resultsmentioning
confidence: 99%
“…19 . Owing to the rarity of the disease and the complexity of its histological classi cation, there is no universally accepted consensus on the management of patients with invasive papillary carcinoma 20 . Interestingly, invasive papillary carcinoma is relatively more prevalent among males 21 which is consistent with our observation of invasive papillary carcinoma breast cancer subtypes in male patients.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical manifestation of EPC mimics a benign breast tumor, as the most common symptom is a palpable breast mass ( 22 , 23 ). As for the tumor size, cases of EPC associated with invasive carcinoma were larger when compared with the non-invasive counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…The IPC has a slow biological activity, tends to progress gradually and has low rates of lymph node and distant organ metastasis. In the current literature, the majority of IPC are classified as luminal type, histologically graded as grade 2 according to the Nottingham system, and have a low TNM stage ( 3 , 24 ). Hashmi et al.…”
Section: Biological Behaviorsmentioning
confidence: 99%
“…The IPC has a slow biological activity, tends to progress gradually and has low rates of lymph node and distant organ metastasis. In the current literature, the majority of IPC are classified as luminal type, histologically graded as grade 2 according to the Nottingham system, and have a low TNM stage (3,24). Hashmi et al retrospectively compared 44 patients with IPC and 1268 patients with IDC and found that IPC had more favorable pathological features than IDC in terms of tumor T stage, axillary lymph node metastasis, Ki-67 index, PR and HER2 expression (25).…”
Section: Biological Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation